Psychotropic medication use in adolescents with intellectual disability living in the community. (8th August 2013) - Doan, Tan; Ware, Robert; McPherson, Lyn; van, Kate; Bain, Christopher; Carrington, Suzanne; Einfeld, Stewart; Tonge, Bruce; Lennox, Nicholas
ABSTRACT Purpose Information on the use of psychotropic medications in adolescents with intellectual disability is scant. Such information can guide interventions to improve psychotropic medication use in this population. We investigated the prevalence of, and factors associated with, psychotropic medication use in adolescents with intellectual disability in Australia who live in the community. Methods Cross‐sectional data were obtained from adolescents with intellectual disability living in the community in South East Queensland, Australia, between February 2007 and September 2010. Self‐reported information on medication use was extracted from a health screening tool. Demographic and medical data were collected through parent/caregiver surveys. Medications were classified according to the Anatomical Therapeutic Chemical classification system. Psychopathology was assessed using the Developmental Behaviour Checklist Short Form. Logistic regression analysis was used to assess the association of demographic and medical characteristics with psychotropic medication use. Results There were 176 participants (median age = 16 years, range = 11–19 years; 55% male). Psychotropics were used by 20% of participants. Psychostimulants were the commonest psychotropic class, used by 9% of participants. Multipsychotropic prescribing was not common with only seven participants using more than one psychotropic agent. After adjusting for potentially confounding variables, use of psychotropic medications was significantly associated with male gender (adjusted odds ratio = 3.6; 95% confidence interval = 1.3–9.5) and having major behaviour problems (3.1; 1.1–8.9). Conclusions Adolescents with intellectual disability use a wide range of psychotropic medications. Being male and having major behaviour problems are associated with the use of psychotropic medications. Research examining the rationale for psychotropic prescribing in this population is needed. Copyright © 2013 John Wiley & Sons, Ltd.